A Creole Synthesis: Archaeology of the Culturally Mixed Heritage Silas Tobias Site in Setauket, New York. (4th May 2019) - Matthews, Christopher N.
ABSTRACT: Research on the Silas Tobias site in Setauket, New York has identified a small nineteenth-century homestead with a well-preserved and stratified archaeological context. Documentation of the site establishes that the site was occupied from at least 1823 until about 1900. Based on documentary evidence, the Tobias family is considered African American, though the mixed Native American and African American heritage of the descendant community is also well-known. Excavations in 2015 exposed both architectural- and midden-associated deposits that shed light on daily life of the Tobias household, which suggests the preservation of Native American cultural practices both in technology and foodways. In essence, the site presents excellent evidence of the mixing of cultural traditions, a process interpreted in this paper as a sign of both political agency of the Tobias family as well as a period of greater tolerance for racial difference associated with the end of slavery in New York.